COGNITIVE LEVEL OF READING QUESTIONS IN ENGLISH TEXTBOOK FOR GRADE XI - Lamtiar Sinaga; Meisuri (Universitas Negeri Medan, 2017)
The objective of the study was to find out the cognitive level of the reading questions in English textbook for grade XI based on the Revised Bloom’s Taxonomy. This study was conducted by using descriptive qualitative method. The data of this research were the reading questions in the English textbook for grade XI Senior High School. The result of this study was the whole reading questions in the textbook covering all of the cognitive levels, they were Remembering (26,02%), Understanding (26,02%), Applying (9,18%), Analyzing (33,16%), Evaluating (1,53%), and Creating (4,08 %).